English for banking - Radice, Francis (Prentice-Hall, 1997)
The book provides practice in the letter-writing skills neede for standard banking transactions, including motivation through progress and archievement tests; variety of text types fro comprehension and as production models; focus on cohesion, lexis, style and meaning; guided writing at sentence, paragraph and whole text level; opportunities for discussion as well as writing